2020
DOI: 10.1007/s00586-020-06310-0
|View full text |Cite
|
Sign up to set email alerts
|

Segmental coupling effects during correction of three-dimensional lumbar deformity using lateral lumbar interbody fusion

Abstract: Purpose Lateral lumbar interbody fusion (LLIF) has been performed to correct spinal deformity associated with lumbar degenerative disease. Although its usefulness has been studied, there are no reports of quantitative evaluation in three dimensions. Our purpose is to quantitate 3D deformity of the patients with lumbar degenerative disease and correction of the deformity by LLIF using patient-specific 3D CT models. Methods We measured the disc height and 3D alignment of the lumbar spine in 28 patients with dege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Previous studies reported the correlation between the coronal Cobb angle and vertebral rotation in adolescent idiopathic scoliosis 10,11) . Additionally, the correlation between wedging deformity and axial rotational deformity in patients with lumbar degenerative scoliosis has been reported previously 12) . However, this is the first report to provide a prediction equation for OMA utilizing the coronal Cobb angle.…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies reported the correlation between the coronal Cobb angle and vertebral rotation in adolescent idiopathic scoliosis 10,11) . Additionally, the correlation between wedging deformity and axial rotational deformity in patients with lumbar degenerative scoliosis has been reported previously 12) . However, this is the first report to provide a prediction equation for OMA utilizing the coronal Cobb angle.…”
Section: Discussionmentioning
confidence: 78%
“…There was no alteration in other spinopelvic parameters, which may be due to the fact that the correction of spinopelvic parameters depends not only on the reduction of listhesis; factors other than vertebral displacement contribute to the resulting spinopelvic parameters. Yamaguchi et al 15 found that there was an increase in lumbar lordosis after vertebral fusion. They revealed that the improvement in one of the spinopelvic parameters was not only caused by changes in postoperative anatomy, but rather the return of spinopelvic parameters to normal values due to complaints of back and leg pain having improved postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed the previous research focusing on the simultaneous motion effects of adult degenerative vertebrae. Yamaguchi et al utilized patient-specific 3D CT models to measure the disc height and 3D alignments, including the wedge, lordosis, and axial rotation angles, at each motion segment ( 20 ). They found positive correlations between the preoperative wedge and the axial rotation angles, as well as between the corrected wedge and the corrected axial rotation angles, which they referred to as “coupled motion”.…”
Section: Discussionmentioning
confidence: 99%